2016
DOI: 10.1080/02687038.2016.1254150
|View full text |Cite
|
Sign up to set email alerts
|

Pain and pain assessment in stroke patients with aphasia: a systematic review

Abstract: Background: Persons with aphasia (PWA) after stroke are less able or unable to communicate about their pain due to language, speech and/or cognitive impairment. Most commonly pain rating scales are used for the assessment of pain in PWA, which could not be applied to any patient aphasia because of their inability to communicate verbally their pain. Aims: This review aims to investigate the prevalence and incidence of pain in PWA after stroke, establish which pain assessment instruments are used, and examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
1
34
0
2
Order By: Relevance
“…A literature review on this topic was recently identified, 11 while other systematic reviews have focused on pain assessment tools for communicative palliative care patients 31 or patients with aphasia. 32 The small sample size of studies contributed significantly to reduce the overall quality scores. Other methodological problems such as the use of a translated but not validated tool also negatively influenced the ratings.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…A literature review on this topic was recently identified, 11 while other systematic reviews have focused on pain assessment tools for communicative palliative care patients 31 or patients with aphasia. 32 The small sample size of studies contributed significantly to reduce the overall quality scores. Other methodological problems such as the use of a translated but not validated tool also negatively influenced the ratings.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Our findings of inconsistent and inconclusive evidence are not unique to stroke. A previous review of pain assessment in aphasia concluded that "a feasible, reliable and valid pain assessment instrument is not yet available" (14). Dementia is another clinical condition where pain is common but potentially difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…As a test of search validity, we pre-specified two papers (one original research and one review) that should be returned on our literature search (1,18). As a further test we cross-checked our included papers with a systematic review of pain assessment in aphasia, recognizing that the topics were distinct but were likely to have considerable overlap (14).…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Hemiplegic pain is one of the types of pain in patients with stroke, with an estimated prevalence of 16% to 84% (7,14,15). Also, in the study by Mazzocato et al 69% of patients had pain (16), and in a review article by de Vries et al it was shown that between 87.3% and 87.8% of patients experienced pain, indicating the importance of pain in these patients (17).…”
Section: Introductionmentioning
confidence: 99%